2022
DOI: 10.1016/j.neuron.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An active vesicle priming machinery suppresses axon regeneration upon adult CNS injury

Abstract: Highlights d Axon growth-competent adult neurons downregulate critical components of the synapse d Pharmacogenetic reduction of neuronal excitability stimulates axon regeneration d The presynaptic active zone proteins Munc13 and RIM suppress axon growth d Systemic Baclofen treatment promotes regeneration after adult spinal cord injury Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 127 publications
5
20
0
Order By: Relevance
“…Therefore, our study suggested that Ezh2 upregulation might rejuvenate mature neurons at the transcriptomic level to empower them with stronger axon regeneration ability. In support of this, several previous studies also demonstrated that suppressed transcription of synaptic function-related genes positively correlated with enhanced axon regeneration ability (Hilton et al ., 2022; Norsworthy et al, 2017; Sekine et al, 2018; Wang et al, 2018b). On the other hand, Ezh2 overexpression also resulted in upregulation of many factors known to enhance axon regeneration, some of which are highly expressed in young developing neurons (Costales and Kolevzon, 2016; Penzo-Mendez, 2010; Zaytseva et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, our study suggested that Ezh2 upregulation might rejuvenate mature neurons at the transcriptomic level to empower them with stronger axon regeneration ability. In support of this, several previous studies also demonstrated that suppressed transcription of synaptic function-related genes positively correlated with enhanced axon regeneration ability (Hilton et al ., 2022; Norsworthy et al, 2017; Sekine et al, 2018; Wang et al, 2018b). On the other hand, Ezh2 overexpression also resulted in upregulation of many factors known to enhance axon regeneration, some of which are highly expressed in young developing neurons (Costales and Kolevzon, 2016; Penzo-Mendez, 2010; Zaytseva et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…A previous study in larval sea lampreys showed that GABA promoted survival and axon regeneration of descending neurons after a complete spinal cord injury through GABA B receptors (Romaus-Sanjurjo et al, 2018). Two recent studies showed that activating GABA B receptors could promote axon regeneration in the mouse dorsal column and cortical spinal tract after spinal cord injury (Hilton et al, 2022; Li et al, 2020). We also investigated the role of Slc6a13 in regenerative axon growth of DRG neurons in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Not only the whole toxins, but also their isolated catalytic domains that are genetically expressed, transfected, or microinjected within target cells have been widely used to study the role of specific SNARE proteins in membrane fusion events, in neurons, in other cell types, and even in animal hosts naturally unsusceptible to their uptake [85][86][87][88][89]. Their use associated with modern biotechnologies still represents a reliable, efficient, and definitely convenient method to block neuroexocytosis in several biological systems [90,91]. Among them, TeNT and BoNT/B and their derivatives, which cleave the identical peptide bond in VAMP-1/2/3, are widely used.…”
Section: Discussionmentioning
confidence: 99%
“…One potential reason could be the apparent incompatibility seen elsewhere in the regenerating nervous system between axon growth and presynaptic maturation. After spinal cord injury in mice, several molecular components of presynaptic release machinery can act as a brake on re-growth in primary sensory axons (Hilton et al, 2021), suggesting that in order to get re-growing axons to their targets, full presynaptic function must be suppressed until the point of synaptic contact. Indeed, genes encoding presynaptic proteins are some of the last to be expressed in OSN development, at least under constitutive conditions (Marcucci et al, 2009; McClintock et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Here even the most successful anatomical regeneration is usually accompanied by incomplete functional synaptic or behavioural recovery, suggestive of a disconnect between experimentally-induced axon regrowth and re-connectivity (Anderson et al, 2018; Ceto et al, 2020; Cheah et al, 2016; De Virgiliis et al, 2020; Fawcett, 2020; Lim et al, 2016; Lu et al, 2012; Wang et al, 2015). Indeed, it was recently shown that certain components of presynaptic release machinery act as a brake on axon regrowth after mammalian spinal cord injury, meaning that molecular mechanisms for promoting growth and those responsible for subsequent functional integration might be diametrically opposed (Hilton et al, 2021). But when even persuading re-growing mammalian central axons to reach their targets is already extremely difficult, how can we determine the additional manipulations required to promote their subsequent re-connectivity?…”
Section: Introductionmentioning
confidence: 99%